Un Nuevo Miliario de la Calzada de la Plata - Rodríguez Hernández, José (Zephyrvs, 2009)
RESUMEN: Un miliario inédito descubierto en San Medel (Salamanca) con el número CXLV, ostenta caracteres de gran rusticidad y difícil lectura. No obstante, puede afirmarse, como resultado de su estudio e interpretación, que corresponde al año 250 ó 251 p. C, ya que el nombre de Dedo aparece asociado con el de Quinto Herennio Etrusco en calidad de César. ABSTRACT: A completely unknown milestone discovered in San Medel (Salamanca) and showing the number CXLV presents characteristics of great rusticity and is of difficult reading. However, we can say with certainty, as result of our study and interpretation, that it corresponds to the year 250 or 251 PC. because the name of Decio appears, associated with that of De Quinto Herennio Etrusco as Cesar.